IMITATING THE EMANCIPATION OF HINDU FEMALE CHARACTERS IN BALINESE WAYANG LEGENDS - Gede Yoga Kharisma Pradana; Ni Made Ruastiti (International Journal of Social Science, 2022)
The purpose of this study was to analyze the role of Hindu women based on the legends of the wayang performance. Many post-colonial Balinese Hindu women began to leave their culture. To be more empowered, they do not have to leave their culture. They are still relevant as role models, like Dewi Anjani, Srikandi, and Dewi Kunti's struggle in the legends. The issues are as follows: (1) What is the image of Dewi Anjani, Srikandi, and Dewi Kunti's struggle? What can be learned from the three Hindu female figures in the legends? All the data was collected through documentation, observation, and interviews with informants in Denpasar. Qualitative-interpretative descriptive analysis is supported by applying symbol, hegemony, and deconstruction theory. The results show that Dewi Anjani is a female character who is able to fight for her rights equal to her two brothers. Srikandi is a female character who is able to fight on par with the leader of the knights on the battlefield. Meanwhile, Dewi Kunti was able to show a firm attitude during the Pandawa conflict. The images of the three figures are role models for the reconstruction of post-colonial Balinese Hindu women in responding to the challenges of globalization.